A coaxial probe with a vertically split outer sensor for charge and dimensional measurement of a passing object - Janne Peltonen; Matti Murtomaa; Aleksi Saikkonen; Jarno Salonen (Elsevier Science BV, 2022)
A coaxial induction probe with a vertically split outer sensor for simultaneously measuring the charge, distance, and size of a passing object is presented. When a charged sphere passed the probe, current signals of different shape induced to all the sensors. The signals were integrated, and Gaussian curves were fitted. The amplitudes and widths of the fitted curves were used to calibrate the set-up. The experimental calibration was done by using frictionally charged spheres of different sizes. Spheres with unknown size, distance, and charge were measured using the calibrated sensor. However, the speed of the object needed to be known. The results from computer simulations, calibrations, and use in measurements are presented.